2020
DOI: 10.1017/s0007114519003350
|View full text |Cite
|
Sign up to set email alerts
|

Severe below-maintenance feed intake increases methane yield from enteric fermentation in cattle

Abstract: AbstractThe relationship between feed intake at production levels and enteric CH4 production in ruminants consuming forage-based diets is well described and considered to be strongly linear. Unlike temperate grazing systems, the intake of ruminants in rain-fed tropical systems is typically below maintenance requirements for part of the year (dry seasons). The relationship between CH4 production and feed intake in animals fed well below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
(33 reference statements)
2
44
1
2
Order By: Relevance
“…We found that propionate production through the acrylate pathway was probably increased while that through the succinate pathway was weakened under SFR condition. Additionally, the enhanced methanogenesis in SFR ewes was in agreement with the report by Goopy et al [ 32 ] who found that severe below-maintenance feed intake increased methane yield in cattle. As well-known that methanogenesis competes the same substrates such as hydrogen with propionate production [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that propionate production through the acrylate pathway was probably increased while that through the succinate pathway was weakened under SFR condition. Additionally, the enhanced methanogenesis in SFR ewes was in agreement with the report by Goopy et al [ 32 ] who found that severe below-maintenance feed intake increased methane yield in cattle. As well-known that methanogenesis competes the same substrates such as hydrogen with propionate production [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…It logically contributes to reducing the uncertainty of GHG emissions estimated at local scale (i.e., from individual farms and farm components) as well as at regional scale. Simultaneously, more recent work aims at testing promising interventions to reduce GHG emissions from agricultural activities (Goopy et al, 2020). A necessity for deriving accurate TIER 2 GHG emissions estimates are detailed household level data which then allow for detailed trade-off analysis between this pillar of CSA as well as the productivity pillar.…”
Section: Pillar 3: Mitigationmentioning
confidence: 99%
“…the result of both grass and cattle interactions which affect rumen fermentation and, as such, represents a convenient basis for estimating enteric methane production. More work is required by research groups in tropical regions on the establishment of robust data sets from which accurate CH 4 yields could be derived for methane inventory purposes (Patra, 2017;Castelán Ortega et al, 2019;Goopy et al, 2020) and for evaluation of effective enteric CH 4 mitigation strategies.…”
Section: Enteric Methane Production By Cattle Fed Tropical Grassesmentioning
confidence: 99%